Smart Tourism Technology and Communication on Rural Destination: Analyze Memorable Experiences, Tourist Satisfaction, and Revisit Intention - Pamuji, Windy Anindya; Sugandini, Dyah; Sutiono, Heru Tri (Jurnal Ilmu Komunikasi, 2024)
The COVID-19 pandemic has caused the tourism and creative economy (Parekraf) sector to experience a significant negative impact. Destinations have an opportunity to build infrastructure for information and communication technology because of the COVID-19 pandemic. The smart tourism communication technology dimensions in this study refer to accessibility communication, informativeness communication, interactivity communication, and personalization communication. Quantitative methods were used with data collected through online questionnaires from 150 respondents and processed using the Partial Least Square programmed. The findings indicate that the four attributes of smart communication tourism technologies – informativeness, accessibility, interactivity, and personalization of communication – contribute to the creation of a pleasant and memorable experience for tourists. This research aids in the creation of a theoretical framework that integrates ME with the idea of smart tourism and mega-events. The results can assist the rural tourism sector in comprehending how smart tourism communication technologies affect travelers' pleasure, experience, and desire to return.